![9x^2+2x-4=0](https://img.qammunity.org/2023/formulas/mathematics/college/b1399ha0wh0gf26r5uyn81z6746kal1bbs.png)
1) We can rewrite that quadratic equation according to the standard form, by performing some algebraic manipulations:^
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
The Standard form, so we can rewrite that equation:
![\begin{gathered} 4-2x=9x^2 \\ 4-2x-9x^2=0 \\ -9x^2-2x+4=0\: /(-1) \\ 9x^2+2x-4=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cgqbgclup60jrw5dy3xffnwqttmmbbdqxk.png)
Note that in order to get that squared term positive, we divided the whole equation by -1
The coefficients are a=9, b= 2, and c=-4